Pengaruh Pendidikan Agama Islam Di Sekolah Terhadap Perilaku Anak Di Rumah Studi Kasus TK Aisyiyah 5 Kota Magelang - Muhammad Nasruddin; Endang Sriwinarsih; Yayah Rukhiyah; Supriyanti Supriyanti; Nginayatul Khasanah (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2021)
PAI at all levels of education aims to increase students' faith, understanding, appreciation and practice of the religion of Islam so that they become Muslim human beings who believe in Allah SWT, and have noble character in personal, social, national and state life. However, there are specific objectives that must be considered so that the influence of Islamic Education at the PAUD level can affect life outside of school and in the family. This quantitative research describes its influence, especially on the students of TK Aisyiyah 5, Magelang City, who identify its significance. For this reason, it is suggested to strengthen the reciprocal relationship between kindergarten and parents in addition to consistency in assisting children in learning Islamic Education at home.